PROVENANCE ANALYSIS OF THE RAMPONG FORMATION SANDSTONE IN THE KETUKAH AREA, GAYO LUES, ACEH - Sartika, Dewi; Gunarsih, Dina; Ahmad, Luthfi; Muhni, Akmal; Rahmatillah, Lia Fitria; Adhari, Muhammad Ridha (Indonesian Physical Review, 2024)
The research location is in Ketukah, Gayo Lues Aceh, which is composed of the Late Oligocene to Early Miocene Rampong Formation. Lithology includes sandstones, conglomerates, and mudstones. The study aims to determine the origin of the sandstones in the Rampong Formation. Provenance studies are beneficial in providing information for oil and gas exploration. The analysis is critical for understanding the sediment transport channel, the overall depositional pattern of the basin, and predicting the location of sand bodies in the basin. Because the Rampong Formation is located in the North Sumatra Basin, the availability of provenance information is useful in efforts to search for oil and gas potential in the future. In this research, we restrict the study to the provenance, which includes the tectonic setting, origin rock, and paleoclimate where these sandstones originate. The methods are geological mapping and petrographic analysis. In petrographic analysis, we use JMicrovision to calculate mineral composition. The results showed that the sandstones of the Rampong Formation are arenite sandstones, especially sub-arkosic and sub-lith arenite. They originate from a tectonic setting known as a recycled orogen, related to the subduction of Eurasia and the Indo-Australian plates.Â  The sandstones were formed from granite that had undergone low metamorphism in the Late Cretaceous to the Eocene period. In addition, the paleoclimate is humid.